Evaluation of Drug Utilization in Patients with Coronary Artery Disease: Prevalence, Predisposing Factors and Prescribing Patterns in Tertiary Care Hospital in Punjab - Sharma, Riya; Thakur, Aman; Sharma, Amit; Kaur, Mandeep; Alqarni, Yousef Saeed; T. Alsulami, Fahad (Indian Journal of Pharmacy Practice)
Background and Objectives: The medication regimens used by patients declared with Coronary Artery Disease (CAD) vary greatly. Our goal was to assess the clinical traits and usage trends in CAD. Assess the factors that influence the occurrence of CAD which ultimately affect the administration of medication in people who have CAD. Materials and Methods: The present prospective research was conducted at the Guru Gobind Singh Medical College and Hospital in Faridkot, Punjab, India, from October 2022 to March 2023 over a six-month period. consent in writing wasn’t required from the participants as no direct interaction with the patient was required. The information was gathered using a unique data gathering form, as well as SPSS by IBM Version 26 was used for analysis. Results: The vast majority of the 152 patients were males, accounting for 82 of them as opposed to the 70 female patients. The study’s sample’s median age ranged from 58 to 69 years. 62.5% of the patients came from rural areas. Only 2% of patients received just one medication, while 68.4% received polypharmacy. The most frequent comorbidity is diabetes and hypertension. Men who drink alcoholic beverages as well as use tobacco products such as cigarettes are more likely to develop CAD. however, most women who refrain from drinking or smoking have been impacted by CAD. Conclusion: The population under study was determined to be inclined to be males, to live in a rural area, as well as be between the ages of 58 and 69. A large proportion of patients received the use of multiple medications (polypharmacy).
Keywords: Coronary artery disease; Drug prescribing pattern; Prevalence; Punjab